2009
DOI: 10.1158/1055-9965.epi-08-0353
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision and Serologically Determined Human Papillomavirus Infection in a Birth Cohort

Abstract: Circumcision has been reported to protect against infection with human papillomavirus (HPV) in men, but results have been inconsistent. We followed males in a birth cohort born in Dunedin, New Zealand, in 1972 and1973 from age 3 to 32 years. Seropositivity at age 32 years for the oncogenic types HPV-16 and 18, and the nononcogenic types 6 and 11, was studied in relation to maternal reports of circumcision status at age 3 for 450 men. Seropositivity to any of these types was associated with lifetime number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…15-16 Many of these observational studies had limited power, were vulnerable to confounding by sexual behaviors in men and women, and evaluated MC status by self-report or the female partner’s report. Moreover, the long latent interval between initial HR-HPV infection and the development of cervical neoplasia complicates causal inferences from retrospective data on prior exposures.…”
Section: Introductionmentioning
confidence: 99%
“…15-16 Many of these observational studies had limited power, were vulnerable to confounding by sexual behaviors in men and women, and evaluated MC status by self-report or the female partner’s report. Moreover, the long latent interval between initial HR-HPV infection and the development of cervical neoplasia complicates causal inferences from retrospective data on prior exposures.…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis of circumcision status and HPV infection that used metaregression also demonstrated that finding an association between HPV and circumcision status was less likely in studies in which sampling the shaft of penis for HPV was performed [7]. A recently published birth cohort study from New Zealand found that the combined seroprevalence of HPV-16 and HPV-18 was not affected by circumcision status (OR, 1.2 [95% CI, 0.75-1.9]) [8]. When studies published since the metaanalysis are included [1,5,6,8] and the analysis is repeated using metaregression, not ascertaining circumcision status by physical examination (OR, 1.77 [95% CI, 1.15-2.73]) and not sampling the penile shaft (OR, 1.57 [95% CI, 1.16-2.12]) are both significantly associated with finding an association between circumcision status and HPV infection.…”
mentioning
confidence: 99%
“…A recently published birth cohort study from New Zealand found that the combined seroprevalence of HPV-16 and HPV-18 was not affected by circumcision status (OR, 1.2 [95% CI, 0.75-1.9]) [8]. When studies published since the metaanalysis are included [1,5,6,8] and the analysis is repeated using metaregression, not ascertaining circumcision status by physical examination (OR, 1.77 [95% CI, 1.15-2.73]) and not sampling the penile shaft (OR, 1.57 [95% CI, 1.16-2.12]) are both significantly associated with finding an association between circumcision status and HPV infection. Adjusting for these 2 factors, the summary OR for circumcision is 0.91 (95% CI, 0.74-1.11), and the difference is not statistically significant.…”
mentioning
confidence: 99%
“…Dave et al Guideline: Foreskin care and neonatal circumcision Dickson et al followed 450 children from birth in a cohort study conducted in New Zealand up to 32 years of age with circumcision status reported by mothers at 3 years of age [98]. Sexual behavior was recorded at 21, 26 and 32 years along with assessment of socioeconomic and moral-religious emphasis of family.…”
Section: Cuaj -Guidelinementioning
confidence: 99%